Model Kontribusi Aset Pengetahuan dalam Memfasilitasi Proses Penciptaan Pengetahuan pada Koperasi Susu - Sukmawati, Anggraini; Maarif, M Syamsul; Marimin, Marimin; Hardjomodjojo, Hartrisari; Indrasti, N S (IPB University, 2010)
Given the crucial role of knowledge creation in contemporary business enterprises, a fundamental question arises: what processes are facilitating knowledge creation? This study aims to find the answer.This study investigates the interrelations among four categories of knowledge assets (experiential, conceptual, systemic, and routine) and four categories of SECI model for knowledge creation processes (socialization, externalization, combination , and internalization). In our framework, we argue that different types of knowledge assets may have differing influences on knowledge creation. In order to test the feasibility of this framework, we conducted an empirical research exercise. Data were collected from three dairy cooperations in Java, Indonesia through a survey instrument. A total of 105 usable responses were analysed. We employed regression analysis, ANOVA and canonical correlation analysis to examine the separate correlations. We identified four responses interrelationhips from this study. Compared to other knowledge assets, conceptual knowledge assets have a greater effect on socialization of knowledge creation process. Experiential knowledge assets have a greater effect on combination. Routine knowledge assets have a greater effect on externalization of knowledge creation process. Systemic knowledge assets have a greater effect on internalization of knowledge creation process.